Sustainable Development Practices in Developing Countries: Major Drivers and Future Discourse - Acharya, Umesh (Nepalese Journal of Development and Rural Studies, 2021)
The objective of this article is to discuss the practices of sustainable development and its challenges in Nepal. Secondary data has been used such as library and documentation materials, and secondary information available. For the proper implementation of sustainable development corruption, free society is essential and the monitoring from people’s side in the development programmesis warranted. Publications of articles related to local governments and Journals published from different research institutes were used. The paper concludes that lack of proper human resources and utilization of natural resources in Nepal is not getting progress in for sustainable development. Nepal government should give emphasis on environment education and awareness programs should be organized in order to preserve natural resources. People’s participation, equity and utilization of indigenous knowledge is vital for the development. At last civil society should have crucial roleto control corruption.Active participation of local bodies and nongovernmental organization also can play vital role for its development with a coordination of ministry of environment and some international organizations.